PENGARUH SOCIAL MEDIA INTERACTION TERHADAP EMOTIONAL ATTACHMENT, BRAND RELATIONSHIP QUALITY DAN WORD OF MOUTH PADA DJAKARTA WAREHOUSE PROJECT - Wendy Sutanto; Siti Rahayu; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2018)
The purpose of this research is to describe the effect of interaction between Djakarta Warehouse Music Project music festival with its consumer using social media to emotional attachment of consumer of the music festival, brand relationship quality between consumer and music festival, and word of mouth that willing to share by consumer of Djakarta Warehouse Music Project. Social media used in this research is facebook, youtube, instagram, path and twitter. The target of respondents in this study is the tourists who have attended the Djakarta Warehouse Project festival. The choice of respondents is intended for information or data obtained for research needs in accordance with the reality (objective). The data obtained in this study comes from the primary data is by distributing questionnaires to consumers. The sample specified in this research is 150 respondents. Data processing methods used in this study include using validity test, reliability test, descriptive statistics, research model test, structural model test and hypothesis testing using SPSS 20.0 and Amos v.20.0 This research got result that interaction between Djakarta Warehouse Project and its consumer by using social media can improve emotional attachment and brand relationship quality which finally influence word of mouth from its consumer.